Pengembangan dan Implementasi Teknologi Serverless Computing pada Sistem Informasi Data Kependudukan Desa dengan Pendekatan Metode Agile - Saputra, Muhammad Dimas Haryo; Dirgahayu, Teduh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Information systems are vital for the collection, storage, and management of data to support decision-making. With technological advancements, serverless computing has emerged as an efficient solution, eliminating the need for manual server infrastructure management and allowing developers to focus on core applications. This study explores the application of serverless technology to enhance administrative efficiency in managing village population data, identifying its benefits and challenges. The research methodology employs an Agile approach, ensuring iterative development and responsiveness to user needs. The results show that serverless computing improves operational efficiency and service quality in population data management. Firebase enables real-time data synchronization without a relational schema. Village officials can manage population events, admins handle user data, and the village head monitors and generates reports. Additionally, system testing confirms that good security and performance enhance data quality. The study provides insights for village governments to adopt serverless technology to improve public services, despite challenges like complex security requirements and managing evolving cloud resources.